Couples and shared leisure experiences. Issue 4 (1st October 2016) - Harmon, Justin
ABSTRACT: This paper explored how romantic couples' involvement in a music scene affected both individual and mutual enjoyment during participation which stimulated the desire for future shared leisure experiences. As all aspects of involvement were seen as largely positive, shared music scene participation served as a vehicle to grow together and strengthen relationships. Through joint participation couples were able to affect their collective well-being in three ways: (1) participation on an individual level led to accrued happiness through lengthy and frequent involvement in an activity that was significantly meaningful and a high priority in each participant's life; (2) participation and interaction with their significant other in the activity that had high value for both led to shared happiness and (3) the shared participation led to greater well-being for the union of the partnership through the existence of mutual friendships, meaningful music and positive experiences of release, recharging and catharsis.